Analisis Relasi Sipil-Militer Guinea Pasca Kudeta Militer Tahun 2021 - Nur Allyah; Y. A. Wahyudin; Zulkarnain Zulkarnain (Department of International Relations, University of Mataram, 2023)
This study aims to provide information and understanding about civil-military relations in Guinea both before the military coup and after the military coup in 2021, as well as how the transition to democracy is in Guinea. This study uses the concept of Transitional Democracy and Pretorianism theory, namely the type of praetorian Arbitrator Army as proposed by Purlmutter and praetorian supervisors as proposed by Nordilinger. The military intervened in civilian affairs temporarily and formed a transitional government and consolidated democracy before being returned to civilians. The result of this study is that bad civil-military relations in the Alpha Conde government and the amendment changes that allowed Alpha Conde to serve as president for the third term became the trigger for the military coup, this military coup was led by colonel Mamady Doumbouya. After the military coup, civil-military relations did not experience significant changes for the better, where the military government committed many violations of democracy and human rights and the military government was unable to fulfill its promise to form a more inclusive government and better elections than before.